Geothermal district heating - Einarsson, Sveinn S. (1973)
Incl. bibl. Chapter on the use of geothermal energy for the heating of houses - Gives as examples Iceland, Hungary, Japan, New Zealand and the USSR, examines certain aspects of the technique of boring and the scientific equipment used, discusses the advantages of geothermal energy as one of the energy resources from the point of view of economics and pollution control